Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3791/54230
|View full text |Cite
|
Sign up to set email alerts
|

How to Study Basement Membrane Stiffness as a Biophysical Trigger in Prostate Cancer and Other Age-related Pathologies or Metabolic Diseases

Abstract: Here we describe a protocol that can be used to study the biophysical microenvironment related to increased thickness and stiffness of the basement membrane (BM) during age-related pathologies and metabolic disorders (e.g. cancer, diabetes, microvascular disease, retinopathy, nephropathy and neuropathy). The premise of the model is non-enzymatic crosslinking of reconstituted BM (rBM) matrix by treatment with glycolaldehyde (GLA) to promote advanced glycation endproduct (AGE) generation via the Maillard reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Because the results indicated that β4E was inducible under RWPE-1 3D growth conditions and was observed in normal epithelial glands in a luminal-type compartment, we next examined whether β4E expression was influenced by tissue culture conditions suitable for epithelial or mesenchymal growth. RWPE-1 cells, as basal stem cells, respond to different media conditions by altering their phenotype (Litvinov et al , 2006; Rodriguez-Teja et al , 2016). Under basal epithelial maintenance conditions, that is, using keratinocyte serum-free media (KSFM), the doxycycline treatment results in a dramatic increase of β4E-tGFP protein expression, from an unexpressed state to expression in 40.8–59% of the population, depending on the concentration of doxycycline, as detected by flow cytometry (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Because the results indicated that β4E was inducible under RWPE-1 3D growth conditions and was observed in normal epithelial glands in a luminal-type compartment, we next examined whether β4E expression was influenced by tissue culture conditions suitable for epithelial or mesenchymal growth. RWPE-1 cells, as basal stem cells, respond to different media conditions by altering their phenotype (Litvinov et al , 2006; Rodriguez-Teja et al , 2016). Under basal epithelial maintenance conditions, that is, using keratinocyte serum-free media (KSFM), the doxycycline treatment results in a dramatic increase of β4E-tGFP protein expression, from an unexpressed state to expression in 40.8–59% of the population, depending on the concentration of doxycycline, as detected by flow cytometry (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%